ダイ 30 ジ ナンキョク チイキ カンソク タイ エットウ タイ ホウコク 1989-1990 - 江尻, 全機; エジリ, マサキ; 召田, 成美; メシダ, シゲミ; Ejiri, Masaki; Meshida, Shigemi (1991)
P(論文) 第30次南極地域観測隊越冬隊37名(昭和基地越冬29名, あすか観測拠点越冬8名)は, 1988年11月14日東京晴海を出航, 1990年3月28日成田に帰着する間, 観測行動実施計画に基づくすべての任務を無事完遂することが出来た。第29次観測隊隕石調査隊の遭難事故救出のため, 一部オペレーションの変更を余儀なくされたが, あすか観測拠点は1988年12月22日から翌12月25日の間, 昭和基地は1989年2月1日から翌1月31日の間, 第30次越冬隊によって両基地の維持・運営・整備を行った。昭和基地では, 第29次観測隊より引き続き実施した定常観測・研究観測のほか, 多目的衛星データ受信システムによる「海洋観測衛星もも1号」「極域超高層探査衛星あけぼの」の受信, 電波星観測, 超長基電波干渉計(VLBI)による南極大陸と日本及びオーストラリアを結ぶ基線決定に世界で初めて成功した。また, 極域周回大気球実験を行った。「南極域における気候変動に関する総合研究」では新たに水平レーダーを設置した。「ヒトの生理学的研究」にも力を注いだ。みずほ基地での高層気象観測も実施した。あすか観測拠点では, 超高層観測, 地上及び高層気象観測, 氷床流動調査, 氷床掘削調査を行うとともに, ヒトの生理学的研究, 氷床上建築物に関する設営工学的計測を引き続き実施した。 The wintering party of the 30th Japanese Antarctic Research Expedition performed its activities at Syowa, Mizuho and Asuka Stations from 1989 to 1990. The wintering party at Syowa Station composed of 29 personnel carried out the routine and fundamental observations comprising aurora, geomagnetism, ionosphere, meteorology, oceanography and seismology. The multipurpose satellite data receiving system was constructed. The telemetry data of EXOS-D (aurora observation satellite) and MOS-1 (Marine Observation Satellite) have been received. This system was also successfully used for radio astronomy as a VLBI (Very Long Baseline Interferometer) to determine precise baselines among Syowa Station in Antarctica, Kashima in Japan, and Tidbinbilla in Australia. The polar patrol balloon was launched and it made a seven-eighth circumpolar orbit at a stratospheric level. As the Antarctic Climate Research programme (ACR), a meteorological PPI radar was newly operated for a continuous observation of clouds and precipitation, in addition to analyses of satellite imagery (NOAA), uninterrupted measurements of CO_2 and CH_4,radiation monitoring, etc. Unmanned and upper-air observations were carried out at Mizuho Station. Natural earthquakes were determined with several seismic sensors including STS sensors around Syowa Station. Studies were made on physiological human activities and environmental sciences. The wintering party at Asuka Station composed ...